Neisseria meningitidis Factor H Binding Protein Surface Exposure on Salmonella Typhimurium GMMA Is Critical to Induce an Effective Immune Response against Both Diseases - Francesca Necchi; Giuseppe Stefanetti; Renzo Alfini; Elena Palmieri; Martina Carducci; Roberta Di Benedetto; Fabiola Schiavo; Maria Grazia Aruta; Fabiola Giusti; Ilaria Ferlenghi; Yun Shan Goh; Simona Rondini; et al. (Pathogens, 2021)
GMMA, outer membrane vesicles resulting from hyperblebbing mutated bacterial strains, are a versatile vaccine platform for displaying both homologous and heterologous antigens. Periplasmic expression is a popular technique for protein expression in the lumen of the blebs. However, the ability of internalized antigens to induce antibody responses has not been extensively investigated. Herein, the Neisseria meningitidis factor H binding protein (fHbp) was heterologously expressed in the lumen of O-antigen positive (OAg+) and O-antigen negative (OAg−) Salmonella Typhimurium GMMA. Only the OAg− GMMA induced an anti-fHbp IgG response in mice if formulated on Alum, although it was weak and much lower compared to the recombinant fHbp. The OAg− GMMA on Alum showed partial instability, with possible exposure of fHbp to the immune system. When we chemically conjugated fHbp to the surface of both OAg+ and OAg− GMMA, these constructs induced a stronger functional response compared to the fHbp immunization alone. Moreover, the OAg+ GMMA construct elicited a strong response against both the target antigens (fHbp and OAg), with no immune interference observed. This result suggests that antigen localization on GMMA surface can play a critical role in the induction of an effective immune response and can encourage the development of GMMA based vaccines delivering key protective antigens on their surface.